Vacuum ultraviolet laser spectroscopy of CO molecules in a supersonic jet - Steinmann, C. M. (Christine Margarete) (Stellenbosch : Stellenbosch University, 2012)
Thesis (PhD)--Stellenbosch University, 2003.